Photoelectrocatalytic hydrolysis of ammonia borane by electrochemical deposited cuprous oxide on titanium dioxide nanotube arrays. (8th March 2022) - Khasanah, Riza Ariyani Nur; Lin, Hui-Ching; Ho, Hsiang-Yun; Peng, Yen-Ping; Hsiao, Hsi-Lien; Wang, Chang-Ren; Chien, Forest Shih-Sen
Abstract: Photoelectrocatalytic hydrolysis of ammonia borane (AB) is a promising technique for producing hydrogen gas (H2 ) in the presence of an appropriate photocatalyst under light irradiation and bias. The application of cuprous oxide on titanium dioxide nanotube arrays (Cu2 O/TNA) for the photoelectrocatalytic hydrolysis of AB was studied. Cu2 O/TNA exhibited a spectral response in the ultraviolet–visible region and an onset wavelength of 600 nm. With AB in an electrolyte, Cu2 O/TNA exhibited a significant increase in its photocurrent spectral response at a bias of 0.1 V versus Ag/AgCl. The H2 generation rate by photoelectrocatalysis (under 5-mW cm −2 irradiation at 455 nm; bias of 0.1 V vs . Ag/AgCl) was 0.018 μmol s −1 cm −2, which was twice that by photocatalysis and four times those by catalysis and electrocatalysis; a Faradaic efficiency of 77% (corresponding to the oxidation reaction of AB) was also observed. Hence, Cu2 O/TNA is an efficient photoanode for photoelectrocatalytic hydrolysis of AB. Graphical abstract: Image 1 Highlights: Cu2 O/TNA is a promising photoanode for photoelectrocatalytic hydrolysis of AB. Cu2 O/TNA performed a significant spectral response at 0.1 V versus Ag/AgCl. H2 generation rate by PEC was twice that by PC and four times those by C and EC. The reaction at 0.1 V versus Ag/AgCl corresponded to the oxidation reaction of AB.